¿A qué nos referimos cuando hablamos del Producto Bruto Interno (PBI)? - Wiener Fresco, Hugo Carlos (2023)
The best known and used indicator of the economy is the Gross Domestic Product. Better than any other, it expresses many dimensions in figures and has a very important role in the decisions-in economic matters. This Academic Note and others that will follow, will try to explain in accessible terms, how it is obtained, what it represents and how it should be interpreted. The perspective adopted in this Note is that as an indicator it maintains its importance and validity and what is required is to develop new economic metrics so as not to exhaust ourselves on the issue of growth, which is a way in which we understand insufficiently the economic development.